2021
DOI: 10.1038/s41598-021-81565-1
|View full text |Cite
|
Sign up to set email alerts
|

Adding a toe joint to a prosthesis: walking biomechanics, energetics, and preference of individuals with unilateral below-knee limb loss

Abstract: Toe joints play an important functional role in able-bodied walking; however, for prosthesis users, the effect of adding a toe joint to a passive prosthetic foot remains largely unknown. The current study explores the kinematics, kinetics, rate of oxygen consumption and user preference of nine individuals with below-knee limb loss. Participants walked on a passive prosthetic foot in two configurations: with a Flexible, articulating toe joint and with a Locked-out toe joint. During level treadmill gait, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The length of the HDP knee joint O knee‐N from the acetabular O hip can be expressed asLOhipOitalickneeNgoodbreak=xOitalickneeN2+yOitalickneeN2According to the properties of parallelograms and the spatial layout shown in Figure 1, taking into account 5 and, 6 we obtainLOhipOitalickneeNgoodbreak=l2goodbreak+l3The distance between the hip and knee joints of the new HDP structure remains constant regardless of the movement of the prosthesis, allowing the new HDP to mimic natural human movement accurately.…”
Section: Bionic Motion Analysis Of the Prosthesis Hip Jointmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of the HDP knee joint O knee‐N from the acetabular O hip can be expressed asLOhipOitalickneeNgoodbreak=xOitalickneeN2+yOitalickneeN2According to the properties of parallelograms and the spatial layout shown in Figure 1, taking into account 5 and, 6 we obtainLOhipOitalickneeNgoodbreak=l2goodbreak+l3The distance between the hip and knee joints of the new HDP structure remains constant regardless of the movement of the prosthesis, allowing the new HDP to mimic natural human movement accurately.…”
Section: Bionic Motion Analysis Of the Prosthesis Hip Jointmentioning
confidence: 99%
“…Among the various prosthetic options, single‐axis hip disarticulation prostheses (HDPs) are commonly used, with the axis of rotation typically positioned anterior to the residual limb at a 45° angle to the coronal plane 1 . Unfortunately, these prostheses' highly asymmetrical lower limb alignment leads to abnormal gait patterns and potential long‐term health issues 4–6 . While several studies have explored advanced intelligent prosthetic control techniques for restoring natural lower limb motion, current designs struggle to accurately replicate biological joint motion characteristics 7–9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led researchers to attempt increasing push-off assistance by attempting to replace the action of the MTP joints by adding a toe-joint. A study by McDonald et al ( 2021 ) added a toe-joint to a passive ankle-foot prosthesis and found no significant differences in kinetics and kinematics. However, a passive foot with a flexible toe-joint by Honert et al ( 2020 ) showed there was a difference using a custom foot with a wider base, longer arch, and a toe-joint.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, amputees’ preferences for prostheses were measured through discrete-choice questions (Hafner et al, 2007; Kahle et al, 2008; McDonald et al, 2021), simple rating (Andrysek et al, 2021), ranking (Klodd et al, 2010), or questionnaire (Raschke et al, 2015). These measures were usually used in between-device comparisons to assess the general perception of the overall performance of the prosthesis but cannot provide information on the preferences for the specific settings.…”
Section: Introductionmentioning
confidence: 99%